Engineering of a novel optimized platform for sublingual delivery with novel characterization tools: in vitro evaluation and in vivo pharmacokinetics study in human - Nadia M. Morsi; Ghada A. Abdelbary; Ahmed H. Elshafeey; M. Abdallah Ahmed (Taylor & Francis Group, 2017)
The aim of this work was to develop a novel and more efficient platform for sublingual drug delivery using mosapride citrate (MSP) as a model drug. The engineering of this delivery system had two stages, the first stage was tuning of MSP physicochemical properties by complexation with pure phosphatidylcholine or phosphatidylinositol enriched soybean lecithin to form MSP-phospholipid complex (MSP-PLCP). Changes in physicochemical properties were assessed and the optimum MSP-PLCP formula was then used for formulation into a flushing resistant platform using two mucoadhesive polymers; sodium alginates and sodium carboxymethylcellulose at different concentrations. Design of experiment approach was used to characterize and optimize the formulated flushing resistant platform. The optimized formulation was then used in a comparative pharmacokinetics study with the market formulation in human volunteers. Results showed a marked change in MSP physicochemical properties of MSP-PLCP compared to MSP. Addition of mucoadhesive polymers to flushing resistant platform at an optimum concentration balanced between desired mucoadhesive properties and a reasonable drug release rate. The optimized formulation showed significantly a superior bioavailability in humans when compared to the market sublingual product. Finally, the novel developed sublingual flushing resistant platform offers a very promising and efficient tool to extend the use of sublingual route and widen its applications.